Issues and Challenges in Teaching Multicultural Music amongst Primary Music Teachers in Malaysia - Yie, Wong Kwan; Ying, Chiu Ming (Malaysian Journal of Music, 2017)
The purpose of this study is to identify the issues and challenges that music teachers face in teaching multicultural music in primary school classrooms in Malaysia. Using a qualitative methodology, in-depth semi-structured interviews were conducted with 30 music teachers from 12 primary schools. The data was analysed using a “themes-based” analysis of narrative. The findings indicate that these music teachers did not have adequate multicultural training during their college courses. The findings also demonstrate that the music teachers believe that multicultural music education is an essential part of music education. However, the implementation can prove to be difficult due to the fact that many music teachers do not possess appropriate multicultural music knowledge and resources in order to teach multicultural music. Music teachers also reported that the activities and approaches used in the classroom must involve the students actively, rather than passively receptive with a need to allow students to obtain first-hand experience playing traditional musical instruments. In particular, the data provides insights into a number of issues and challenges that music teachers face in implementing multicultural practices in Malaysian primary school music programmes. Hence, music teacher training programmes must take into account the diversity of Malaysian society in order to prepare music teachers to be receptive, tolerant and sensitive to the inclusion of multicultural music in their teaching.